The cortical component of experience-dependent synaptic plasticity in the rat barrel cortex - Fox, K (J Neurosci, 1994)
Rats were raised with altered tactile experience from P0 by removing all but one vibrissa (D1) from one side of the face (D1-spared animals). This procedure (univibrissa rearing) has previously been shown to cause neurons in cortical barrels surrounding D1 to develop greater than normal responses to D1 vibrissa stimulation and smaller than normal responses to principal vibrissa stimulation (Fox, 1992). In this study, it was found that the potentiated D1 responses could be attenuated by acute microlesions placed in the D1 barrel, while principal vibrissa responses were unchanged or even slightly elevated for the same cases. The ratio of the average D1 to principal vibrissa response was approximately proportional to the volume of tissue damaged in the D1 barrel. This result implies that the synaptic plasticity seen in cortex of D1-spared animals is due to synaptic changes that take place within the barrel cortex rather than to relay of changes occurring at a subcortical level. In addition, lesions aimed at the septum between D1 and an adjacent barrel almost completely abolished responses to D1 stimulation in that barrel, including short-latency responses (5–10 msec). Only neurons severed horizontally from D1 were affected. Neurons that maintained a connection with the D1 barrel via a bridge of septal tissue preserved their usual elevated levels of response to D1 stimulation and their aberrant short-latency responses. This result implies that pathways radiating out from the D1 barrel/column, and connecting neurons in the D1 barrel to cells in surrounding barrels, undergo synaptic plasticity induced by univibrissa rearing.